Effect of cloned human interferons on protein synthesis and morphogenesis of herpes simplex virus. - Chatterjee, S (1985)
Pretreatment of human fibroblast cells with 100 U of either cloned human alpha-2 or beta interferon per ml for 24 h reduced the release of infectious herpes simplex virus type 1 by more than 99%. This inhibition in infectivity correlated well with the total number of extracellular virus particles released from treated cells as determined by DNA dot blot hybridization analysis. Electron microscopic observations of interferon-treated human fibroblast cells clearly demonstrated typical assembly of nucleocapsids inside the nucleus, even though very few mature extracellular particles were seen. Analysis of virus-specific proteins by the immunoblot technique showed that neither species of interferon had a significant inhibitory effect on the synthesis of major nucleocapsid proteins. However, the synthesis of specific glycoproteins (D and B) was drastically reduced or delayed in beta-interferon-treated cells. The results presented in this communication suggest that cloned human interferons block herpes simplex virus morphogenesis at a late stage and inhibit the release of particles from the treated cells.